2015
DOI: 10.1111/dote.12336
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity and the risk of Barrett's esophagus

Abstract: Physical activity either directly or through influencing body fat may affect the risk of Barrett's esophagus (BE). However, the effect of physical activity on the risk of developing BE has not been examined. We conducted a case-control study among consecutive eligible patients either scheduled for elective endoscopy or recruited from primary care clinics to undergo a study endoscopy. Study participants completed the International Physical Activity Questionnaire (IPAQ) short form that measures physical activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Thirteen studies were excluded, as they did not provide sufficient data (reasons for exclusion detailed in Appendix ). Data were extracted from 83 studies; however, 11 of these studies had to be excluded from the statistical analysis as they contained data from same populations already described in other articles . Our final statistical analysis included 72 studies.…”
Section: Resultsmentioning
confidence: 99%
“…Thirteen studies were excluded, as they did not provide sufficient data (reasons for exclusion detailed in Appendix ). Data were extracted from 83 studies; however, 11 of these studies had to be excluded from the statistical analysis as they contained data from same populations already described in other articles . Our final statistical analysis included 72 studies.…”
Section: Resultsmentioning
confidence: 99%
“…The authors reported no association between the highest vs. lowest levels of physical activity and odds of Barrett's oesophagus (OR = 1.19, 95% CI 0.82-1.73). 39 The statistical model used in the study adjusted for age, sex, race, GORD symptoms, Helicobacter pylori infection status (which may reduce risk if positive), BMI and high waist to hip ratio (WHR).…”
Section: Resultsmentioning
confidence: 99%
“…The exposure was measured using the International Physical Activity Questionnaire (IPAQ), which measures the previous 7 days recreational exercise. The authors reported no association between the highest vs. lowest levels of physical activity and odds of Barrett's oesophagus (OR = 1.19, 95% CI 0.82-1.73) [17]. Limitations of this study included the potential for measurement error by using a 7 day measure of physical activity in symptomatic individuals and the limited generalisability of war veterans.…”
Section: Discussionmentioning
confidence: 84%
“…The evidence for occupational activity from these studies was inconsistent [13,14]. To date, only one study has investigated Barrett's oesophagus and reported no association between recreational exercise and disease risk (occupational activity was not measured) [17]. Our aim was to investigate, for the first time in a prospective cohort study, the relationship between both occupational and recreational levels of physical activity and the incidence of Barrett's oesophagus.…”
Section: Introductionmentioning
confidence: 98%